TEACHERS AND STUDENTS ACTING TOGETHER IN THE DEVELOPMENT OF A PROJECT ON HUMAN RIGHTS AND RACISM - Klein, Ana Maria [UNESP]; Silva, Mariana Dutra da; Aires Pedrosa, Priscilla Bernardes [UNESP] (Fundacao Univ Tocantins, 2019)
This article is the result of a project developed by a team that involved a researcher, two teachers from the state of Sao Paulo, three undergraduate students in Pedagogy with scholarships of Scientific Initiation-PIBIC, financed by CNPq teachers and students of the Secondary School of a state school in the interior of the state of Sao Paulo. The project was developed through pedagogical actions and perceptions survey carried out with high school students of a state school in the interior of the state of Sao Paulo. The objective was to discuss with students the feelings of people who experience and / or witness biased and racist attitudes. The article reports on the project development process.
Keywords: Human rights; Teacher; Racism